Cohesive Devices Analysis In Abstract Journal Of Premise Volume 6 Number 2 In 2017 - Fitri Palupi K; Rizki Aziza (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The aims of this research are to explain how reference and reiteration distribute to the text, and also to know the numbers of occurrences and percentages of reference and reiteration found in the text. The subject of this research is 10 Abstracts of PREMISE Journal of English Education Volume 6 Number 2 of Teacher Training and Education Faculty of Muhammadiyah University of Metro summit on October 2017 in Metro, Lampung. The object of this research is components of grammatical and lexical cohesion in reference and reiteration which are developed by Halliday and Hasan. This research is qualitative research. The result shows that almost all elements of the cohesion available in the abstracts. The total number of cohesion in the abstract is 318; consist of 254 reference types and 64 reiteration types. The percentages from each type are 9.8% personal reference, 63.8% demonstrative reference, and 6.3% comparative reference in reference types. Besides that, there are 17.3% repetition, 2.2% synonymy, 0% metonymy, and 0.3% for hyponymy and antonymy in reiteration types. The researcher concluded that the highest cohesive device in the text is a demonstrative reference. The use of cohesive devices found in abstracts is to connect one sentence to another.